THE IMPACT OF COVID-19 ON CONTINUED LEARNING IN THE MIDDLE EAST, EASTERN AND SOUTHERN AFRICA (MEESA) REGION - Ouma, George; Machonesa, Angela; Kapaso, Bevis; Chikonde , Nkonde (African Journal of Education and Practice, 2022)
Purpose: The purpose of this study was to establish the impact of covid-19 on continued learning in the Middle East, Eastern and Southern Africa (MEESA) region. Materials and Methods: Using appreciative inquiry methods, the study conducted 2-7 in-country key informant interviews and 2 focus groups in select countries across diverse geographies and perspectives. Focus group discussions were assembled through the support of Plan International and its network of organizations providing education support to children, adolescent girls, and young women. The purposive sampling procedure was utilized on the evaluation to have a targeted reach of relevant stakeholders on the training based on Plan Internationals network in-country. Ultimately, a reasonable sample was drawn with the goal of reaching saturation for reliable inference. A total of 20 interviews were conducted, which includes 6 KII and 14 FGDs. The digital platforms used were Zoom and Microsoft Teams.These conversations were recorded and stored for use during analysis. The qualitative findings on this evaluation were coded with ideas and thoughts noted during the process of data collection using a thematic approach to qualitative analysis. After data collection from the 5 countries, the data was transcribed and arranged in order of the respective research questions that were asked and based on the interview topic guide. Results: The findings indicate that following COVID-19 lockdowns and implementation of further restrictions, all the countries of focus experienced closure of schools at least once between March 2020 and March 2021. This resulted in disruption on learning particularly for adolescent girls and young women. Unique contribution to theory, practice and policy: The study recommends that the governments should prioritize the education of all children, including the most marginalised, the emphasis was on encouraging governments to assess the response of institutions and enabling education to continue in some form outside its traditional setting.Enhance multi-level and multisectoral response for continued access to learning during a pandemic such as COVID-19 by strengthening education technical working groups working on continued access to learning.